Literatur Review : Hubungan Pengetahuan dengan Perilaku Personal Hygiene Menstruasi Remaja Putri - Anggita Fajariyani; Luvi Dian Afriyani; Andri Yani; Ivana Sika Yon; Maria Karmelia Wung Song; Valentina Brigita Dewi (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2022)
Menstrual hygiene is a component of personal hygiene, which plays an important role in a person's health behavior status. This includes avoiding interference with the reproductive organs' function. Objective: This research aims to determine the results of a literature review study, that is the relationship between knowledge and personal hygiene behavior during menstruation for teenage girls. Method: This research employed the literature review method by collecting 4 research journal articles. The keyword used the identification in the PEOS format and determined the inclusion and exclusion criteria for the journal to be selected. The article search was conducted using two databases (Google Scholar and PubMed), and JBI was used to assess the suitability of the journal selection. Results: Two of the four articles stated that adolescents' knowledge of adolescent personal hygiene behavior in menstruation was good, while the other two stated that adolescents' knowledge of menstrual personal hygiene behavior was lacking. Conclusions and Suggestions: There is a relationship between knowledge and menstrual personal hygiene. There is also relationship between behavior and menstrual personal hygiene. Further research on this theme and development of research can be done by adding variables and then using more databases. Abstrak Latar belakang: Hygiene pada saat menstruasi merupakan komponen personal hygiene (kebersihan perorangan) yang berperan penting dalam status perilaku kesehatan seseorang. Termasuk menghindari adanya gangguan pada fungsi alat reproduksi. Tujuan: Untuk mengetahui hasil study literatur review, antara pengetahuan dengan perilaku personal hygiene saat menstruasi remaja putri. Metode penelitian: Menggunakan metode literatur review, dengan mengumpulkan 4 jurnal artikel penelitian, menggunakan identifikasi kata kunci dengan format PEOS dan menentukan kriteria jurnal yang akan dipilih dengan menggunakan kriteria inklusi dan ekslusi. Pencarian artikel dilakukan pada dua database (Google Schoolar dan Pubmed), serta menggunakan JBI untuk kesesuaian penilaian pemilihan jurnal. Hasil penelitian: Dari 4 artikel, 2 artikel diantaranya menyatakan remaja dengan pengetahuan remaja dengan perilaku personal hygiene menstruasi adalah baik, dan 2 artikel menyatakan pengetahuan remaja dengan perilaku personal hygiene menstruasi adalah kurang. Kesimpulan dan saran: Ada hubungan antara pengetahuan dengan personal hygiene menstruasi, adanya hubungan antara perilaku dengan personal hygiene menstruasi. Peneliti selanjutnya dapat meneliti mengenai tema ini dan mengembangkan penelitian dengan menambah variabel dan selanjutnya dapat menggunakan database yang lebih banyak.